IMPLEMENTASI METODE DRILL DALAM MENGHAFAL SURAT PENDEK AL-QUR’AN: STUDI KUALITATIF DI SDI IBN HAJAR BANTAR GEBANG BEKASI - Sa?adah, Nur; Abas, Munir (Turats, 2016)
The aim of this research is to know about the implementation of the Drill Method in memorizing the short letter of Qur?an in Sekolah Dasar Islam (the Islamic Elementary School) Ibn Hajar Bantar Gebang Bekasi. By this qualitative study can be concluded that the implementation of the Drill Method in memorizing a Qur?anic short letter was done through the following steps : (1) The teacher makes an example firstly by reading one verse in front of the class with a clear voice and reading; (2) The teacher reads the passage back and all the students are required to follow the the teacher?s readings ; (3) If the readings have been sounded eloquent, fluent and correct, the the teacher asks all the male students to recite the exemplified verses then continued by the female students. These steps should continuously be repeated until the goal can be achieved. The obstacles of application of the method is that the provision of Drill Method repetitively often make students become bored or fed. The results of the study explained that the Drill Method in memorizing the Qur?anic short letter proven to provide training and increasing in memorizing Qur?anic short letter in a day a student can be able to produce two short verses and for as much as one long paragraph. In one school year or 141 times of the effective meetings can generate as many as 16 letters or memorizing 97 verses